Birds symbols in Aljazeeri divan - Ziyab, Abu Obaid (Humanities Journal of University of Zakho, 2020)
The world is full of beautiful sounds, colors and wonderful views that were created by the Almighty. Human beings were able to name and show the features of everything around the world. However, it is quite normal the existence of a number of ambiguous daily terms that need a special language in order to facilitate the comprehension process. It refers to that language as a symbolic language to express the importance of the various meanings. A number of symbols and ambiguous terms exist which reflect its significance in highlighting and unveiling that hidden world just like the way how the Sufi imagine but cannot express the events by using an ordinary and simple languageThe use of "birds" as a symbol of Sufi has become a reason for creating a meaningful writing as well as Sufi poetry adorned/decorated with poetic words. In this context, birds have been found in the Al-Jaziri`s collection of poems and each one carries a special symbol based on the natural features and characteristics. This research paves the way to identify these birds, as well as to unveil their characteristics related to symbolic subjects according to the Sufi poetry. It also attempts to clarify the hidden meanings behind these symbols for each bird’s nameThis research consists of an introduction and two main sections, the first section deals with the theoretical framework on symbolism, while the second section deals with the practical aspect of the symbols used for birds in Al Jaziri’s collection poems. Finally, it deals with the most important results of the study.